Sosialisasi Gerakan Gemar Menabung Sejak Dini pada Siswa/Siswi Sekolah Dasar Negeri 027 Kota Bangun - Jofachri, Muhammad; Ahmad, Islamudin (Jurnal Abdita Naturafarm, 2024)
This community service aims to provide elementary school students with an understanding of the importance of saving. It is also hoped that it can contribute to educating the younger generation with an awareness of saving from an early age. By saving, every child will learn to be independent and not depend on their parents. Saving habits will be better if they get encouragement and motivation from parents. The method of implementing community service is carried out through 'socialization'. Partners in this activity are SDN 027 Kota Bangun, Kota Bangun III Village, Kota Bangun Darat District, Kutai Kartanegara. The number of students who took part in the activity was 30 people, namely those from class IV. The results of this activity are expected to increase interest in saving among elementary school students in Kota Bangun III Village